Specific issues related to the law of corresponding states for the charge transport in molecular junctions based on graphene electrodes - Bâldea, Ioan (Applied surface science, 2019)
A recent Science paper in the field of graphene-based molecular electronics reported on fabrication of molecular photoswitches with unprecedented levels of accuracy, reproducibility, and stability. Current-voltage curves measured for diarylethene junctions with graphene electrode were found to agree with a law of corresponding states (LCS) deduced theoretically for the nanotransport via tunneling and validated against a variety of molecular junctions with metallic electrodes. In this work, we discuss a series of specific aspects related to the applicability of this LCS to junctions with graphene electrodes, e.g., what is the physical motivation of the width of the bias range wherein experimental data were found to agree with the aforementioned LCS. The analysis presented in this paper emphasizes the essential role played in nanotransport by interactions at molecule-electrode interfaces as well as the fact that a significant impact of temperature is compatible with a transport mechanism via tunneling; temperature dependence does not necessarily imply a transport mechanism via hopping, contrary to what is often claimed.